The gender gap, education, and the life cycle profile in the Brazilian formal labour market - Cecilia Machado; Marcelo Cortes Neri; Valdemar Rodrigues de Pinho Neto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We study the trajectory of the gender gap over time and over the life cycle, using a matched employer-employee data from the formal labour market in Brazil. We document the evolution of participation and earnings for both males and females during the period 1994-2015 and the gender earnings gap throughout the life cycle for different birth cohorts. We focus on the cohort of workers (male and female) born between 1967 and 1974, who were working in 1994, in order to understand the roles that occupation/industry and establishment play on the gender gap pattern throughout the life cycle and for different education levels. We find that the gender earnings gap increases with the educational level. For instance, at 40 years of age, women without high school degrees earned on average 28.8 per cent less than men with the same level of education and for the group with high school and college degrees, this difference was 32.6 and 47.4 per cent, respectively. After controlling for the occupation/industry and firm's characteristics, we observe a remaining gender earnings gap lower than 20 per cent and greater than 10 per cent over the entire career and independent of the educational level.
Keywords: I24; J31; 330; earnings inequality; linked employer-employee data; education; Brazilian inequality; entropy indexes; firms' effects